Navigating the doctorate: a reflection on the journey of ‘becoming’ a PhD in applied language sciences - Mark Nartey (Taylor & Francis Group, 2021)
In the last two decades, academic reflections on the PhD experience and studies on various aspects of doctoral research education have attracted scholarly attention in the higher education and advanced academic literacy literature. In this article, I adopt a reflective-narrative framework to recount my engagement with the doctoral program at The Hong Kong Polytechnic University. I discuss how I tackled specific aspects of the PhD and thesis: choosing a topic/title for my project, writing the abstract, undertaking the literature review, conducting the analysis and my experience with the writing process. I also highlight the challenges I faced, how I overcame them and the insights I gained from them, thereby illustrating how doctoral narratives can be empowering and provide inspiration to current and future doctoral students. The experiences I recount reveal the complex nature of the doctorate as both an individual and a collective endeavor. Implications of the paper for the scholarship on narrative inquiry, doctoral thesis writing and academic identity are discussed.